A Flexible Indeterminate Theory of Religion: Thinking through Chinese Religious Phenomena - Woo, Tak-ling Terry (Religions, 2019)
This essay explores a few of the reasons for the failure of Western theories to capture Chinese religious experiences. It will include Durkheim's insight that "The sacred ... is society in disguised form" and variants of secularization theories in contrast to Confucian ones, especially Xunzi's theory about ritual, read as representative of religion. This article will examine the impossibility of asserting a straightforward claim, without exception, that could capture the three thousand years of historical and contemporary diversity manifested by the three institutional religions (Confucianism, Daoism, and Buddhism), the continuous formation of popular religious movements, ever developing sectarian groups, and pan-Chinese quasi-religious practices like ancestor veneration, divination, healing practices and the like. The study will start by looking at variable categories used in the study of different religions, the similarities in assumptions among the three institutional religions such as the "good" and self-cultivation, and the central place of secularization theory in the contemporary study of Chinese religions. A theoretical orientation of both flexibility and indeterminacy is suggested based on indigenous ideas.